2021
DOI: 10.1002/mp.15195
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in ensuring the generalizability of image quantitation methods for MRI

Abstract: Image quantitation methods including quantitative MRI, multiparametric MRI, and radiomics offer great promise for clinical use. However, many of these methods have limited clinical adoption, in part due to issues of generalizability, that is, the ability to translate methods and models across institutions. Researchers can assess generalizability through measurement of repeatability and reproducibility, thus quantifying different aspects of measurement variance. In this article, we review the challenges to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Quantitative MRI and deep learning deviations from normal tissue values could be detected prior to the manifestation of visible morphological changes (Keenan et al, 2019(Keenan et al, , 2022. In particular, several studies have shown the potential of MR relaxometry (qMRI) in clinical applications (Cashmore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative MRI and deep learning deviations from normal tissue values could be detected prior to the manifestation of visible morphological changes (Keenan et al, 2019(Keenan et al, , 2022. In particular, several studies have shown the potential of MR relaxometry (qMRI) in clinical applications (Cashmore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…By measuring tissue properties, quantitative MRI has the possibility of complementing the morphological analysis currently performed by clinicians on conventional images with quantitative information from normal and abnormal tissue. In addition, it could also aid early diagnosis since deviations from normal tissue values could be detected prior to the manifestation of visible morphological changes (Keenan et al, 2019, 2022). In particular, several studies have shown the potential of MR relaxometry (qMRI) in clinical applications (Cashmore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…By measuring tissue properties, quantitative MRI has the possibility of complementing the morphological analysis currently performed by clinicians on conventional images with quantitative information from normal and abnormal tissue. In addition, it could also aid early diagnosis since deviations from normal tissue values could be detected prior to the manifestation of visible morphological changes (Keenan et al 2019(Keenan et al , 2022. In particular, several studies have shown the potential of MR relaxometry (qMRI) in clinical applications (Cashmore et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…MR thermometry as an alternative approach suffers from a coarse temperature resolution [22]. The advent of artificial intelligence (AI) and machine learning in MRI [23][24][25][26][27][28][29][30][31][32][33][34][35][36] has opened up new avenues for the prediction of various imaging characteristics, among them the recent prediction of local SAR in prostate imaging [37][38][39][40], as well as the prediction of temperature rise in the brain for 33 different tissue types [41].…”
Section: Introductionmentioning
confidence: 99%